Turnover Intention in Manufacturing Industry: SEM-PLS Analysis. - Yeoh, Phee Hooi; Ibrahim, Zahari (2020)
This study intends to examine the influence of hygiene factors and motivation factors of Herzberg’s Two Factors Theory on turnover intention among the shop floor employees in manufacturing organizations. Quantitative research design has deployed with survey questionnaires in this study and the respondents’ data were analyzed with Statistical Package for Social Sciences version 21 (SPSS) and Smart PLS software. The results of the study found that motivational factors are critical in between the hypothesized relationships to shop floor employees’ turnover intention. From the hypothesis modelling, the research concluded that the shop floor employees’ turnover intention was influenced by salary, co-worker, advancement and work itself. This study opts to give insight information to the management in manufacturing organizations. Further, this study provided discussion and implication from the findings and suggestions for future research.